2021
DOI: 10.1111/and.14125
|View full text |Cite
|
Sign up to set email alerts
|

Laser enucleation for prostates larger than 100 mL: Comparison of HoLEP and ThuLEP

Abstract: Summary Recently, with the advancements in laser technology, Holmium laser enucleation of the prostate (HoLEP) and Thulium laser enucleation of the prostate (ThuLEP) have come to the fore in the surgical treatment of benign prostatic hyperplasia (BPH). We aimed to evaluate and compare the outcomes of HoLEP and ThuLEP in patients with >100 ml prostate volume. Patients who underwent HoLEP and ThuLEP between July 2017 and March 2020 were reviewed retrospectively. The patients were divided into two groups as HoLEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…However, ThuLEP was superior in terms of total operative time, laser efficiency, enucleation time, and enucleation efficiency. 41 Compared to Bozzini et al, 49 no significant differences were found in terms of postoperative stress incontinence or AUR.…”
Section: Thuep Vs Holepmentioning
confidence: 70%
See 4 more Smart Citations
“…However, ThuLEP was superior in terms of total operative time, laser efficiency, enucleation time, and enucleation efficiency. 41 Compared to Bozzini et al, 49 no significant differences were found in terms of postoperative stress incontinence or AUR.…”
Section: Thuep Vs Holepmentioning
confidence: 70%
“…Various studies have shown the feasibility and efficacy of ThuEP in the treatment of large prostates. [37][38][39][40][41] One study by Becker et al 39,42 showed that outcomes were sustained at 4-year follow-up with only 1/90 patients requiring retreatment and 3/90 patients requiring treatment for urethral stricture or bladder neck contraction. Nevertheless, very few studies comparing ThuEP and OP were found in our research.…”
Section: Thuep Vs Opmentioning
confidence: 99%
See 3 more Smart Citations